PENGEMBANGAN FORMULA BODY LOTION EKSTRAK KAYU MANIS (Cinnamomum burmannii) SEBAGAI PELEMBAB : UJI EFEKTIVITAS MENGGUNAKAN SKIN MOISTURE ANALYZER - Siampa, Jainer; Papu, Adelfia; Jayanto, Imam (Sam Ratulangi University, 2024)
Nowadays, modern society's activities are mostly carried out outside, so the harmful effects of changes in temperature, exposure to UV radiation, pollution and air humidity, namely a decrease or even loss of skin moisture, cannot be avoided. If untreated, reduced moisture in the skin will not only make the skin scaly, but will also cause irritation or injury to the skin. This research aimed to test the moisturizing effect of the best body lotion formula and also test irritation and hedonics. This test had received ethical approval and was carried out on the same panelists and the moisturizing effect of the preparation was measured using a skin moisture analyzer. The results obtained show that the formulation could increase the moisture of the panelists' skin by 56% and irritation testing showed no redness and swelling. So it can be concluded that the cinnamon extract body lotion formula had a moisturizing effect and not irritating so it was harmless to apply on the skin.